P-296 Examining the link between environmental toxin exposure and uterine leiomyoma: a systematic review. (6th August 2021) - Sodhi, J; Chan, L; Chow, R; Chen, I
Abstract: Study question: Is there an association between exposure to certain environmental toxins and the prevalence of uterine leiomyoma in women? Summary answer: Some evidence was obtained to suggest an association between phthalate esters, bisphenol A, heavy metals, persistent organic pollutants and the prevalence of uterine fibroids. What is known already: Environmental toxins are naturally occurring, or human made chemicals that can act as endocrine disrupting chemicals (EDCs) by binding and activating estrogen receptors in the body. Uterine fibroids, often called leiomyoma are non-cancerous growths occurring in the uterus. Though often asymptomatic, they can cause pain, infertility, pregnancy complications and are a leading cause for hysterectomy. The aetiology of leiomyoma is not fully understood but both estrogen and progesterone have been implicated in their growth. We aimed to investigate the epidemiological evidence for the association between EDCs and the prevalence of fibroids.  Study design, size, duration: We undertook a systematic review and in keeping with PRISMA guidelines, a structured search of Medline, Embase, Scopus, and Web of Science was conducted (to October 2020). Case-control, cross-sectional, cohort and experimental studies were included.  Participants/materials, setting, methods: The included studies analyzed the association between one or more toxins and the occurrence, or growth of leiomyoma in humans, including human cell lines. The types of toxins, patient characteristics, association and outcome, body concentration of toxin and confounding variables were extracted and analyzed. Quality assessment was performed using the Newcastle-Ottawa Scale. Main results and the role of chance: In total, 34 studies were included. The majority (76%) of studies revealed a significant association between the exposure studied and the prevalence of uterine leiomyoma. In examining body burden in cases vs controls, phthalate esters showed an association with increased odds of uterine leiomyoma, except in one case where a negative association was observed. In vitro experimental studies examining the effect of alkyl-phenols such as bisphenol A (BPA), octylphenol (OP) and nonylphenol (NP) demonstrated that these environmental estrogens can act to promote the proliferation of leiomyoma cells through a number of mechanisms, typically including the estrogen receptor alpha (ERa) signalling pathway. There were conflicting results for the association between alkyl-phenols and fibroids in case-control studies. A positive association between cadmium was demonstrated in only two studies. There were conflicting results for the association between lead, mercury, arsenic and uterine fibroids. Several metabolites of organophosphate esters, alternative plasticizers, and persistent organic pollutants were associated with an increased risk of uterine fibroids.  Limitations, reasons for caution: Separating these exposures from the multiple other factors that could affect the outcome of leiomyoma is challenging, but an important issue for future research.  Wider implications of the findings: The link between some environmental toxins and uterine fibroids discussed is in agreement with previous literature. However, our review provides a more in depth analysis on specific dosage effects, odds ratios, and potential gene mechanisms of the exposures. This information could contribute to more accurate preventative measures. Trial registration number: not applicable